Galileo's Problem with PRS or What's in a Phase?. (23rd January 2012) - Hodgart, M. Stephen
Abstract : The upcoming Galileo global navigation satellite system has a design problem with the cosine-phased BOCc(15, 2.5) modulation of its Public Regulated Service (PRS A-code). This signal needs far more bandwidth than the available 40.92 MHz. The present signal and system specification cannot be expected to deliver design performance under practical operational conditions (noise, receiver phase distortion, and multipath). There would not have been this problem with sine-phased BOC(15, 2.5).